Coupling effect between heat flux distribution and buoyancy of supercritical CO2 heat transfer with nonuniform heat flux in parabolic-trough collector. (October 2022) - Xu, Yunting; Tian, Ran; Dai, Xiaoye; Shi, Lin
Highlights: sCO2 heat transfer with non-uniform heat flux in PTC was analyzed. Two uniform heat flux conditions are compared with the non-uniform one. Supercritical CO2 leads to better heat transfer ability and uniformity. Coupling relation between heat flux and buoyancy effect varies with solar elevation. Abstract: To promote the development of concentrating solar power generation technology using supercritical CO2 (sCO2 ), the heat transfer under non-uniform heat flux in the parabolic-trough collector was numerically simulated with emphasis on the coupling effect of the heat flux distribution, the property variations and the buoyancy effect. The non-uniform heat flux effect was first analyzed by comparing with two typical uniform heat flux conditions, which showed that the non-uniform heat flux reduced the overall heat transfer rate below that of the average uniform heat flux. Neither the average nor the maximum heat flux predictions could accurately reflect the heat transfer uniformity characteristics with the non-uniform heat flux. The circumferential non-uniformity was underestimated even with the maximum heat flux. Then, the analysis of the interaction between property variations and buoyancy effect showed that the use of sCO2 improves the heat transfer rate. The buoyancy effect dominates in modifying the flow field, which always enlarges the difference between top and bottom. The specific heat and viscosity variation effects are canceled out by the thermal conductivity variation. The buoyancy presents a negative effect on heat transfer when acting alone, but improves the heat transfer ability and their uniformity when coupled with the other property variations. Finally, the heat flux distribution effect coupled with the buoyancy effect was analyzed through changing the solar elevation angles. The maximum heat transfer coefficient is always located near the tube bottom due to the secondary flow effect. The circumferential non-uniformity increases with increasing Δ θ as the relationship between heat flux distribution and the buoyancy effects change from competing to synergistic.